2012
DOI: 10.3748/wjg.v18.i48.7378
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary fiber on constipation: A meta analysis

Abstract: Dietary fiber intake can obviously increase stool frequency in patients with constipation. It does not obviously improve stool consistency, treatment success, laxative use and painful defecation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
136
1
16

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(157 citation statements)
references
References 25 publications
4
136
1
16
Order By: Relevance
“…84 However, it is not clear that dietary fiber improves stool consistency, treatment success, laxative use, or painful defecation. 83 15. Statement: Dietary fiber intake is an initial strategy in the management of chronic constipation because it has some benefits, is easy to implement, is low cost, and there is little risk of serious adverse events.…”
Section: Statement: Dietary Fiber Can Increase Stool Frequency In Patmentioning
confidence: 99%
See 1 more Smart Citation
“…84 However, it is not clear that dietary fiber improves stool consistency, treatment success, laxative use, or painful defecation. 83 15. Statement: Dietary fiber intake is an initial strategy in the management of chronic constipation because it has some benefits, is easy to implement, is low cost, and there is little risk of serious adverse events.…”
Section: Statement: Dietary Fiber Can Increase Stool Frequency In Patmentioning
confidence: 99%
“…82 A recent meta-analysis concluded that dietary fiber intake can clearly increase stool frequency in patients with constipation. 83 Naturally occurring fiber types include soluble highly fermentable oligosaccharides (eg, fructo-oligosaccharides and galactooligosaccharides), soluble highly fermentable fiber (eg, resistant starch, pectin, guar gum), intermediate soluble fermentable fiber (eg, psyllium and oats), insoluble slowly fermentable fiber (eg, wheat bran, fruit, and vegetables), and insoluble non-fermentable fiber (eg, cellulose and sterculia). 81 Good laxative effects were observed in intermediate soluble fermentable fibers, insoluble slowly fermentable fibers, and insoluble non-fermentable fibers.…”
Section: Statement: Dietary Fiber Can Increase Stool Frequency In Patmentioning
confidence: 99%
“…Yang et al (61) undertook a meta-analysis of five good-quality randomised controlled trials that compared the effects of dietary fibre interventions with placebo in patients with constipation. Three of the included randomised controlled trials used glucomannan, one wheat bran, and one cocoa husk.…”
Section: Gastrointestinal Healthmentioning
confidence: 99%
“…A meta-analysis demonstrated that dietary fiber can increase stool frequency in patients with constipation but also showed that dietary fiber did not improve stool consistency, treatment success, laxative use and painful defecation 8 . On the consumption of fruits there are very few studies.…”
Section: Exclusion Criteriamentioning
confidence: 99%